2013
DOI: 10.1093/brain/awt162
|View full text |Cite
|
Sign up to set email alerts
|

The role of the posterior cingulate cortex in cognition and disease

Abstract: The posterior cingulate cortex is a highly connected and metabolically active brain region. Recent studies suggest it has an important cognitive role, although there is no consensus about what this is. The region is typically discussed as having a unitary function because of a common pattern of relative deactivation observed during attentionally demanding tasks. One influential hypothesis is that the posterior cingulate cortex has a central role in supporting internally-directed cognition. It is a key node in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

104
1,462
6
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,858 publications
(1,623 citation statements)
references
References 171 publications
104
1,462
6
7
Order By: Relevance
“…Currently, we cannot distinguish whether the relation is specific for MS or physiological, as MuSIC subscores were not determined in our HC group and none of the mean values of the MuSIC subscores differed significantly from those given in the original publication on MuSIC 22. Nevertheless, our finding corresponds with cognitive deficits in patients having suffered from damage to the posterior cingulate cortex 36. This relation is commonly explained by the finding that the posterior cingulate cortex is an important hub in the default mode network, which is also altered in MS 44, 45…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Currently, we cannot distinguish whether the relation is specific for MS or physiological, as MuSIC subscores were not determined in our HC group and none of the mean values of the MuSIC subscores differed significantly from those given in the original publication on MuSIC 22. Nevertheless, our finding corresponds with cognitive deficits in patients having suffered from damage to the posterior cingulate cortex 36. This relation is commonly explained by the finding that the posterior cingulate cortex is an important hub in the default mode network, which is also altered in MS 44, 45…”
Section: Discussionsupporting
confidence: 73%
“…The posterior cingulate is assumed to play a central role for internally directed cognition, retrieval of memory, and attention,36 which are in part covered by our clinical scores (see Table 2). Because correlation between the cluster values of the left and right posterior cingulate cortex was high ( R 2  = 0.7) and because we had no hypothesis on lateralized effects, we used the individual mean values (collapsed across hemispheres) of both clusters for correlation with the 12 clinical scores given in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The dorsal PCC also showed greater functional connectivity between the left CMA in the PTSD+DS group as compared with the PTSD − DS group. Generally, the PCC has been shown to be associated with visuospatial orientation that is mediated through its extensive parietal lobe connections and assessment of self-relevant sensations (Vogt and Laureys, 2005), and recently it has been suggested that the dorsal PCC is involved in conscious, awareness, and attention (Leech and Sharp, 2014). Moreover, the dorsal PCC is implicated in orienting the body toward innocuous and noxious somatosensory stimuli and mediates nociception, the encoding and processing of harmful stimuli (Vogt and Laureys, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Anterior cingulate/medial superior frontal cortex has been identified as a key region that implements “task sets”, setting brain state in a domain independent manner 20, 21. Posterior cingulate cortex, a major hub of the default mode network, plays a central role in cognition, modulating interactions between the default mode network and cognitive networks that are important for task performance 22. Furthermore, steady state connectivity analyses in epilepsy have repeatedly pointed to the presence of dysfunction within the default mode network 23…”
Section: Introductionmentioning
confidence: 99%